Adaptability of Islamic Banking across the EU Regarding Public Lending - – the United Kingdom and the Slovak Republic - Adamcová, Barbora; Štěrbová, Ludmila, 1957-; Bruckner, Bernulf; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
Islamic banking belongs to the fastest growing areas of the global financial sector. The banks have already entered the EU market and operate in several highly multicultural member states. However, in other parts of the EU, the system is still not brought into existence. Due to the perceived dependency of Islamic banks on the Muslim minorities, concerns are raised about the ability of the financial system to operate in countries with low multiculturality. The thesis aims to evaluate the extent of adaptability of Islamic financing solutions in the financial markets of highly multicultural and low multicultural EU member states, more specifically, in the UK and Slovakia. Empirical data was collected through the means of semi-structured interviews and analysed by qualitative content analysis. Findings indicate that the extent of adaptability of Islamic financing products is limited to the usage by Muslim customers. There is only a minimal demand by other customer segments. Therefore, Islamic banks should focus on the improvement of product attractiveness and awareness, in order to expand operations and survive in highly multicultural countries. In low-multicultural member states, the opportunities are negligible; however, product attractiveness and educating customers would be prerequisites for entering the market.
Vedoucí práce: Ludmila Štěrbová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses